ÙÙØ¨ÙØ§Ø¯ÙØ¦Ù Ø§ÙØ´ÙÙØ±ÙÙÙØ¹ÙØ©Ù Ø§ÙÙØ¥ÙØ³ÙÙØ§ÙÙÙÙÙÙØ©Ù ÙÙÙÙÙ Ø¶ÙÙÙØ¡Ù Ø§ÙÙÙÙØ±ÙØ¢ÙÙ Ø§ÙÙÙÙØ±ÙÙÙÙÙ ÙÙØ§ÙØ³ÙÙÙÙÙØ©Ù Ø§ÙÙÙÙØ¨ÙÙÙÙÙÙØ©Ù - Hamzah, Andi Abdul (DIKTUM: Jurnal Syariah dan Hukum, 2016)
This paper discusses the principles of Islamic Sharia by analyzing the verses of the Quran, hadith, and some explanations of the scholars of fiqh. The principles of Islamic Sharia include justice, freedom, shura, humanely, fraternity and solidarity. Islamic civilization built on these principles has existed for several centuries ago in Asia, Africa, and Europe and it contributes greatly to humans and humanity in the form of prosperity, happiness, security, and prosperity to all mankind.